Dietary supplementation with corn distillers’ dried grains with solubles improves egg quality in Haidong chickens by promoting beneficial gut microbiota and modulating serum biochemical profiles - Bao, Gaoliang; Wei, Hong; He, Decang; Wang, Dejun; Ding, Baoan; Zhang, Junxia; Tian, Jiayu; Wang, Pengshun; Shen, Baolin (Frontiers in Microbiology, 2025)
Gut microbial metabolism plays a critical role in modulating egg quality through its influence on host serum physiology. Recent evidence suggests that distillers’ dried grains with solubles (DDGS) exhibit prebiotic properties by promoting beneficial gut microbiota while suppressing pathogenic bacteria, thereby enhancing intestinal microbial homeostasis. This study investigated the impacts of dietary DDGS supplementation on egg quality, serum physiological-biochemical indices, and gut microbial communities in Haidong chickens. A total of 288 hens were randomly allocated to six dietary treatments containing 0, 2.5, 5.0, 7.5, 10.0, and 12.5% DDGS for 90 days, followed by the collection of eggs, serum samples, and intestinal contents for analysis. The results indicated that 12.5% DDGS supplementation significantly improved egg albumen height and egg weight (p < 0.05). Concurrently, serum analyses revealed enhanced immune indices, elevated protein metabolism markers, increased high density lipoprotein (HDL) and high density lipoprotein cholesterol (HDL-C) levels, and up-regulated anti-inflammatory cytokine IL-10. Conversely, the 12.5% DDGS group exhibited reduced lipid parameters, decreased liver function marker ALT, and down-regulated pro-inflammatory cytokines (p < 0.05). Gut microbiota profiling showed that the 12.5% DDGS group significantly increased the relative abundances of Firmicutes and Lactobacillus (p < 0.05). Moreover, Lactobacillus pontis and Romboutsia ilealis are associated with enhanced gut immunity and dietary nutrient metabolism, as well as host growth and developmental processes, contributing to the observed improvements in egg quality. These findings establish DDGS as a functional feed additive that improves poultry productivity through microbiota-mediated mechanisms, providing valuable insights for its application in sustainable animal husbandry practices.